ON CHINESE STUDENTS NAVIGATING INTERCULTURAL AND EMOTIONAL BORDERS IN TESOL CLASSES IN A PORTUGUESE POLYTECHNIC - Daubney , Mark (Revista Conhecimento Online: Diversidade e Inclusão Social, 2024)
This study, part of a larger project exploring the multiple impacts that a one-year study abroad programme at a Portuguese higher education institution had on Chinese students, looks at how these students perceived and managed their experiences both in and outside the classroom. This paper focuses on their classroom experience, and has two central aims: firstly, to explore how this study abroad programme impacted students; secondly, to explore preconceptions identified in the literature regarding Chinese students which might constrain the mindsets and behaviour of Portuguese teachers and students towards these. The results of this qualitative study – deploying exploratory practice and a combined longitudinal and ethnographic approach – point to how a key experience of these Chinese students was learning how to navigate multiple borders – linguistic, cultural, political, and emotional – in an immersive language setting.